Matthias Erzberger, 1875 - 1921: Patriot und Visionär - Palmer, Christoph E.; Schnabel, Thomas (Hohenheim-Verlag, 2007)
Literaturverz. S. 241 - 260
Literaturverzeichnis S. 241 - 260
Keywords: Erzberger, Matthias -- 1875-1921; Germany -- Politics and government -- 1888-1918; Aufsatzsammlung; Biografie; Erzberger, Matthias